A new validated stability-indicating gradient RP-HPLC method for the determination of pemetrexed disodium and its process related substances - Hemchand, S.; Babu, R. Ravi Chandra; Annapurna, Mukthinuthalapati Mathrusri (Journal of Drug Delivery and Therapeutics, 2019)
Pemetrexed disodium is used for the treatment of malignant pleural mesothelioma and lung cancer. In the present study a simple stability indicating RP-HPLC method was developed and validated for the determination of Pemetrexed disodium. The process related substances such as Dimer-1 impurity, Dimer-2 impurity, N-Methyl Pemetrexed, Pemetrexed diethyl ester, Alanine derivative of Pemetrexed, DMF derivative of Pemetrexed, Acid intermediate, Oxidation impurity and D-isomer were separated on gradient mode and quantified. Forced degradation studies were performed to prove the specificity. Hypersil BDS C18 100 x 4.6mm, 3µm was used for the separation (at 27°C) with mobile phase mixture consisting of (0.02M sodium dihydrogen phosphate with 0.1% HCOOH and pH 3.8 with dilute sodium hydroxide): Acetonitrile (40:60 v/v) (pH 3.8) with a flow rate of 1.2 mL/min. Methanol: water (1:1) was used as diluent and the eluted compounds were monitored at 240 nm. 0.5-1500 µg/mL with linear regression equation y = 20588x - 9294.1 (R2=0.9999). The degradation products observed during the forced degradation studies were well resolved from the drug peak and proving that the method is a stability-indicating method. The method was validated as per ICH guidelines. Keywords: Pemetrexed disodium, RP-HPLC, gradient mode, Related substances, Stability indicating, Validation.